2012
DOI: 10.1016/j.chroma.2011.12.099
|View full text |Cite
|
Sign up to set email alerts
|

Development of a carbon clad core-shell silica for high speed two-dimensional liquid chromatography

Abstract: We recently introduced a new method ([1]) to deposit carbon on fully porous silicas (5 μm) to address some of the shortcomings of carbon clad zirconia (C/ZrO2), which has rather low retention due to its low surface area (20–30 m2/g). The method enables the introduction of a thin, homogeneous layer of Al (III) on silica to serve as catalytic sites for carbon deposition without damaging the silica’s native pore structure. Subsequent carbon deposition by chemical vapor deposition resulted in chromatographically u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 47 publications
1
22
0
Order By: Relevance
“…1,2 The fines are removed by flotation. The slurry of 5 g of CCSi particles in 250 mL of THF are sonicated for 5 minutes, followed by gentle shaking and then left to settle slowly.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 The fines are removed by flotation. The slurry of 5 g of CCSi particles in 250 mL of THF are sonicated for 5 minutes, followed by gentle shaking and then left to settle slowly.…”
Section: Methodsmentioning
confidence: 99%
“…1,2 In that method, we showed that very close to exactly one uniform monolayer of Al (III) was deposited on the silica by a process analogous to precipitation from homogeneous solution in order to preclude pore blockage. The purpose of the Al(III) monolayer layer is to activate the surface for subsequent CVD of carbon.…”
mentioning
confidence: 99%
“…For instance, the hybrid HILIC phase achieved h of 1.9 (95,000 plates m −1 ) which is about eight times lower than the carboxylate-PGC column (h ∼ 15.5) for BTMA. This hybrid carbon-silica phase shows improved efficiency as compared to the recently developed carbon clad core-shell silica phase (h ∼ 2.5) [27].…”
Section: Efficiency Of the Hybrid Carbon-silica Phasementioning
confidence: 96%
“…The carbon load on typical RPLC and HILIC Halo core-shell silica particles ranges from 3.5 to 8.2% w/w [30]. Carbon clad core-shell silica phases, created by vapor deposition process, have up to 7% w/w [27]. From the XPS data (Supplementary Table S2), the surface concentration of carbon increased from 33.2 to 35.5 at% C. The surface % N decreased from 1.58% to 1.33%, indicating that the latex AS9-SC coated core-shell silica is covered by the carbon nanoparticles.…”
Section: Physical Characterization Of the Hybrid Carbon-silica Phasementioning
confidence: 99%
See 1 more Smart Citation